18F-Sodium Fluoride PET/CT in Oncology. (April 2015) - Sabbah, Nathanael; Jackson, Tatianie; Mosci, Camila; Jamali, Mehran; Minamimoto, Ryogo; Quon, Andrew; Mittra, Erik S.; Iagaru, Andrei
<x xml:space="preserve">Abstract</x> Purpose The purpose of this study was to analyze the distribution of 18F Sodium Fluoride (18F-NaF) uptake in the normal skeleton, benign and malignant bone lesions, and extraskeletal tissues, using semiquantitative SUV measurements. Patients and Methods We retrospectively analyzed data from 129 patients who had 18F-NaF PET/CT at our institution for an oncological diagnosis between 2007 and 2014. There were 99 men and 30 women, 19 to 90 years old (mean [SD], 61.5 [15.5]). The range, average, and SD of SUV were measured for normal bone and extraskeletal tissues uptake for the entire patient population. A separate statistical analysis was performed to compare group A, which corresponds to the population of patient with no 18F-NaF–avid metastatic lesions, and group B, which corresponds to the population of patient with 18F-NaF–avid metastatic lesions. We also measured SUVmax and SUVmean for bony metastases and degenerative changes Results The PET/CT images were acquired at 30 to 169 minutes (mean [SD], 76.5 [22.8]) after injection of 3.9 to 13.6 mCi (mean [SD], 7.3 [2.4]) of 18F-NaF. The range and mean (SD) of SUVmax for 18F-NaF–avid metastasis were 4.5 to 103.3 and 25.9 (16.6) and for 18F-NaF–avid degenerative changes were 3.3 to 52.1 and 16.5 (7.9), respectively. Conclusions Various skeletal sites have different normal SUVs. Skeletal metastases have different SUVs when compared with benign findings such as degenerative changes.